Theoretical foundations and main stages of the transformation of the digitalization of the economy - Shakeyev, S.S.; Nevmatulina K.А.; Vladimirov, Zh. (BUKETOV BUSINESS REVIEW, 2021)
Object: The relevance of the article is due to the fact that the modern economy is entering an innovative stage of development, and a person with his potential, knowledge, creative thinking, and experience is gaining more and more importance. In the context of the development of the fourth scientific and technological revolution and global digitalization, the usual processes are being transformed and simplified — this is the simplification of access of the population and business to public services, and the acceleration of information exchange, and the emergence of new opportunities for doing business, the creation of new digital products, etc. Over the past decades, the world has been rapidly moving towards a new type of economy, where digital technologies are becoming the main tool for its formation. The expansion of the role of information technology in the work of the private and public sectors is the basis for the transition to a digital state. Methods: The comparative analysis method used by the authors in the study confirmed the relevance and relevance of digitalization problems, arising from the necessary and irreversible transformation in the digital economy, the introduction of modern digital technologies, resulting the high efficiency of the economy as a whole. Results: To achieve this goal, the authors analyzed theoretical approaches to the concept of “digital economy”, investigated the stages and principles of the transformation of society in the context of the development and formation of Industry 4.0. Conclusions: As a result of the study, the authors have formed the concept of a digital economy, analyzed the impact of global digitalization on the socio-cultural transformation of society, identified the main indicators of a digital society, determined the stages and principles of transformation of the digitalization process.